Robust Band-Pass Filter-Based PLL-Less Approach for Three-Phase Nonsinusoidal Grid Conditions - Manish Kumar; Anant Kumar Verma; Claudio Burgos-Mellado; Raj Kumar Jarial; Ravinder Nath; Bhumaiah Jula; Diego Munoz-Carpintero; Catalina Gonzalez-Castano; Pedro Roncero-Sanchez (IEEE Open Journal of Instrumentation and Measurement)
The performance enhancement of an inverter-based grid-connected system necessitates a fast and accurate dynamic response in terms of estimating three-phase grid voltage attributes. The synchronous reference frame phase-locked loop (PLL) and/or the frequency-locking (i.e., frequency-locked loop) approaches are widely used in practical applications. However, due to the phase/frequency feedback loops, the aforementioned parameter estimation schemes may experience instability and provide a slow dynamic response. This work presents a PLL-less grid synchronization solution for three-phase applications to counter the slower dynamic response and demonstrate better immunity against the nonideality of a three-phase grid. In order to remove even and odd-order harmonics and extract the fundamental frequency positive sequence (FFPS), the proposed method employs a combination of band pass filters (CBPFs). Additionally, a novel frequency estimation algorithm is developed, which accurately estimates the angular three-phase grid frequency. Furthermore, the phase angle and amplitude are adaptively estimated using an off-line error-resolving approach, which is derived from the transfer function of the proposed prefiltering solution. Finally, the experimental findings validate the robustness of the current proposal.